Reevaluating the Legal Status of Monosodium Glutamate Consumption: The Indonesian Ulema Council’s Fatwas and Maqāṣid al-Sharī’ah - Syam, Syafruddin; Permata, Cahaya; Haris, Rizki Muhammad; Matondang, Maulidya Mora (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This article examines the consistency of the MUI Fatwa regarding Monosodium Glutamate (MSG) from a Maqāṣid al-Sharī’ah standpoint. The legal issue addressed in this research arises from the ongoing debate regarding the consumption of MSG. The Indonesian Ulema Council (MUI) has issued a fatwa declaring that MSG consumption is permissible (halal), provided that it is produced from halal ingredients and is processed, packaged, marketed, distributed, and served in compliance with Islamic law. However, numerous studies have highlighted the adverse effects associated with MSG consumption. This research employs a normative-empirical approach to Islamic law. The primary normative data consists of the MUI fatwa concerning flavoring products, specifically monosodium glutamate, which contains amino acids, as well as various sources discussing Maqāṣid al-Sharī’ah. The primary empirical data is derived from interviews with MUI board members regarding their perspectives on the relevant fatwa. Additionally, non-legal sources, including scientific literature on MSG, are utilized. Through this methodological approach, the research yielded several key findings. Although the MUI has declared MSG consumption as halal, individuals must still adhere to the safety guidelines established by the WHO and the Indonesian Ministry of Health. The MUI further advises against excessive or prolonged consumption of MSG due to its harmful effects on one’s well-being, including the soul, mind, reproductive system, beliefs, and property, all of which Islamic law mandates to be safeguarded. Consequently, the research concludes that the MUI fatwa, along with the explanations provided by its members, aligns closely with the principles of Maqāṣid al-Sharī’ah, as the prevention of harm takes precedence over the pursuit of benefits.